The Effect of the Discovery Learning Model Assisted by Mind Mapping on Students' Metacognition Ability - Kesumawardani, Aryani Dwi; Wati, Cindy Ira; Sari, Aulia Novita; Fiani, Raicha Okta; Wati, Eka Rina; Sawitri, Endang (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
This study aims to determine the influence of the Discovery Learning model assisted by Mind Mapping on students' metacognition ability in Biology subjects. This study is a quantitative research with a quasi-experimental design. The sampling method employed was the cluster random sampling technique. The data collection techniques were the test and questionnaires. The data analysis techniques used were the t-test and N-Gain test. The t-test obtained a significance value (sig) of 0.000 > 0.05 (less than 0.05). It means that H1 was accepted and H0 was rejected. Based on the average N-Gain scores, the test and questionnaire results indicated that metacognitive ability was higher in the experimental class (60.58) with an